An Insight into the Diverse Roles of Surfactant Proteins, SP-A and SP-D in Innate and Adaptive Immunity - Nayak, Annapurna; Dodagatta-Marri, Eswari; Tsolaki, Anthony G.; Kishore, Uday (Frontiers in Immunology, 2012)
Pulmonary surfactant proteins, SP-A and SP-D, are hydrophilic collagen-containing calcium-dependent lectins, which appear to have a range of innate immune functions at pulmonary as well as extrapulmonary sites. These proteins bind to target ligands on pathogens, allergens and apoptotic cells via C-terminal carbohydrate recognition domains while the collagen region brings about the effector functions. SP-A and SP-D deals with various pathogens triggering a range of innate immune mechanisms such as agglutination/aggregation, enhancement of phagocytosis and killing reactions, and growth inhibition. SP-A and SP-D have also been involved in the control of pulmonary inflammation including allergy and asthma, and hence, they are likely to central issues in a range of pathological situations. There is also emerging evidence to suggest that SP-A and SP-D are capable of linking innate immunity with adaptive immunity that includes modulation of dendritic cell function and helper T cell polarisation. It is clear now that SP-A and SP-D are potent innate immune molecules in the lungs. This review is a summary of their immunological properties in general and their importance in human health and disease.